KEMAMPUAN BERPIKIR KREATIF MENGGUNAKAN PMRI PADA SISWA SMP - Sari, Lovika Dinda; Widyaningrum, Indah; Rahayu, Chika (Universitas Bhinneka PGRI, 2024)
The purpose of this study is to identify the impact of creative thinking skills using PMRI on grade VIII students. The method used is an experimental method with a pretest-posttest control research design group. The research sample involved the random selection of two classes, namely class VIII.6 (Experimental Class) with a total of 29 students and class VIII.3 (Control Class) with the same number of students. Data was collected using documentation methods, observation sheets, and essay tests. The results of this study obtained the average score of the experimental class which was 87 and the average of the control class 76. Then the average results of students' creative thinking skills for the four indicators were obtained in the experimental class of 77% which was categorized as good and the control class had an average of 60% which was categorized as adequate. The data was processed using Soffware SPSS version 25. From Equal Variances Assumed and Equal Variances Not Ascetic, the value of sig (2-tailed) is 0.000 0.05, then it is rejected and accepted. So that the ability to think creatively using PMRI in students has a good effect on the learning process of junior high school students